The Anomaly of Entrapment - Jessica A. Roth (Washington University Law Review, 2014)
Now in our second decade after 9/11, we are firmly in the prevention era of law enforcement. Faced with the unacceptable consequences of identifying threats too late, government agents are moving aggressively to identify potential terrorists before they strike. Undercover agents and confidential informants necessarily play a large role in such efforts. As a result of such operations, we have seen a number of cases brought to trial in the federal courts in which defendants have asserted the entrapment defense. To date, the defense has not succeeded. However, as a consequence of these cases, the United States Supreme Court may be required to reconsider the defense for the first time in over twenty years. Thus, now is a good time to re-examine the entrapment defense that the Supreme Court first recognized eighty years ago. This Article argues that the federal entrapment defense represents a doctrinal anomaly that straddles the line between criminal procedure and criminal substance. Understanding how and why the entrapment defense evolved as it did may engender greater sympathy for this much-maligned corner of the criminal law. It could also lead to reforms in the way the defense is administered that would better serve the interests that animate the defense—some sounding in the traditional concerns of substantive criminal law (culpability and dangerousness) and others in the traditional concerns of criminal procedure (deterring overzealous and unwarranted intrusions by government agents).
Keywords: law enforcement; terrorism; confidential information; entrapment; doctrinal anomaly; criminal procedure; criminal substance; deterrence; culpability; intrusions